Respuesta :

Answer:

third answer

Step-by-step explanation:

-9x < 63

divide by nine

-x< 7

multiply by -1

x > -7

C. x>-7 is the final answer.

First you had to multiply by negative one (-1) from both sides of equation.

And it gave us ⇒ [tex](-9x)(-1)>63(-1)[/tex]

And then simplify.

And it gave us ⇒ [tex]9x>-63[/tex]

Next you divide by nine (9) from both sides of equation.

And it gave us ⇒ [tex]\frac{9x}{9}>\frac{-63}{9}[/tex]

Simplify.

[tex]\frac{9x}{9}=x[/tex]

[tex]\frac{-63}{9}=-7[/tex]

[tex]x>-7[/tex]

x>-7 is the final answer.

Hope this helps! And thank you for posting your question at here on brainly, and have a great day. -Charlie

ACCESS MORE